(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The study of toponymy has garnered increasing attention in linguistic research as place names serve as cultural markers reflecting historical, social, and linguistic transformations. This article aims to examine the intertoponymic relations between Termez (Uzbekistan) and Winchester (United Kingdom), focusing on the comparative analysis of place names. The research utilizes linguistic, historical, and cultural approaches to analyze the origin, evolution, and semantic aspects of toponyms in both cities. By identifying similarities and differences, the study contributes to the broader understanding of toponymic patterns across distinct linguistic and cultural environments.